Dejanski in želeni vpliv monografij Leopoldine Plut Pregelj na poslušanje v slovenski šoli - Bešter, Marja (Jezik in slovstvo, 2015)
The development of listening ability has been included in the Slovenian language curriculum in primary and secondary schools since 1998, due in part to the impact of the book Learning by Listening (1990) by Leopoldina Plut Pregelj, the first monograph on listening skills in Slovenia. The updated and expanded edition of this work was published in 2012 under the title Listening - A Way of Life and a Source of Knowing, and it is interesting to consider whether the new edition can also contribute to improving the quality of (Slovenian language) lessons.
Keywords: Plut-Pregelj, Leopoldina, 1946-; Plut Pregelj, Leopoldina: Poslušanje - način življenja in vir znanja; Slovene; slovenščina; jezikovna didaktika; poslušanje; učni pogovor